Co-delivery of D-(KLAKLAK)2 Peptide and Chlorin e6 using a Liposomal Complex for Synergistic Cancer Therapy - Chaemin Lim; Jin Kook Kang; Woong Roeck Won; June Yong Park; Sang Myung Han; Thi ngoc Le; Jae Chang Kim; Jaewon Her; Yuseon Shin; Kyung Taek Oh (MDPI AG, 2019)
Nanotechnology-based photo-chemo combination therapy has been extensively investigated to improve therapeutic outcomes in anticancer treatment. Specifically, with the help of a singlet oxygen generated by the photosensitizer, the endocytosed nanoparticles are allowed to escape from the endosomal compartment, which is currently an obstacle in nanotechnology-based anticancer therapy. In this study, a liposomal complex system (Lipo (Pep, Ce6)), composed of a chlorin e6-conjugated di-block copolymer (PEG-PLL(-g-Ce6)) and a D-(KLAKLAK)2 peptide loading liposome (Lipo (Pep)), was developed and evaluated for its anticancer activity. Due to the membrane lytic ability of the D-(KLAKLAK)2 peptide and the membrane disruptive effect of the singlet oxygen generated from chlorin e6, Lipo (Pep, Ce6) accelerated the disruption of the endosomal compartment, and exhibited strong synergistic anticancer activity in vitro. The prepared liposomal complex system could potentially maximize the efficacy of the nanotechnology-based photo-chemo combination therapy, and can be regarded as a novel, versatile strategy in advanced tumor therapy.